2015
DOI: 10.1177/1049732315578400
|View full text |Cite
|
Sign up to set email alerts
|

Medical Residents’ Experiences With Medically Unexplained Illness and Medically Unexplained Symptoms

Abstract: Patients who present with medically unexplained illnesses or medically unexplained symptoms (MUI/S) tend to be higher utilizers of health care services and have significantly greater health care costs than other patients, which add stress and strain for both the patient and provider. Although MUI/S are commonly seen in primary care, there is not sufficient information available regarding how providers can increase their level of confidence and decrease their level of frustration when working with patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…FM is a medically unexplained and “contested illness,” which means it sits at the bottom of the illness “prestige” hierarchy within medicine (Album & Westin, 2008; Moss & Teghtsoonian, 2008). In addition, previous research on medical professionals’ perspectives reveal that they are frustrated by contested and medically unexplained diagnoses, and that FM might be particularly problematic for health care practitioners (Colmenares-Roa et al, 2016; Harsh et al, 2015). In part, this is because FM does not refer to a specific disease entity, meaning it falls outside of orthodox medical models of disease, and this makes it difficult for doctors to comprehend and treat (Bass & Henderson, 2014; Hellström, Bullington, Karlsson, Lindqvist, & Mattsson, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FM is a medically unexplained and “contested illness,” which means it sits at the bottom of the illness “prestige” hierarchy within medicine (Album & Westin, 2008; Moss & Teghtsoonian, 2008). In addition, previous research on medical professionals’ perspectives reveal that they are frustrated by contested and medically unexplained diagnoses, and that FM might be particularly problematic for health care practitioners (Colmenares-Roa et al, 2016; Harsh et al, 2015). In part, this is because FM does not refer to a specific disease entity, meaning it falls outside of orthodox medical models of disease, and this makes it difficult for doctors to comprehend and treat (Bass & Henderson, 2014; Hellström, Bullington, Karlsson, Lindqvist, & Mattsson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…While a medical diagnosis is desired by patients, studies have found that the process of getting a diagnosis is highly problematic for people with nonvisible symptoms, and it can make doctor–patient interactions frustrating for both doctors and patients (Harsh, Hodgson, White, Lamson, & Irons, 2015; Sim & Madden, 2008; Werner & Malterud, 2003). Yet the desire for a diagnosis and the credibility it confers is argued to be why many people with chronic conditions are willing to “fight” for a diagnosis (Dumit, 2006), by enduring countless tests, consulting multiple health professionals, and engaging in various strategies to influence control and power within the medical encounter (Asbring & Narvanen, 2004; Skuladottir & Halldorsdottir, 2008; Werner & Malterud, 2003).…”
Section: Sociology Of Diagnosismentioning
confidence: 99%
“…In the literature, the dismissive attitudes that medical professionals display toward their patients often appear unintentional (Thesen, 2005). Doctors treating patients with MUS express frustration regarding their situations as well (Harsh, Hodgson, White, Lamson, & Irons, 2016). Bearing this in mind, it would be constructive for further ethnographic studies to focus both on patients seeking accurate diagnoses and their doctors concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…From the health care professionals’ perspective, patients with MUS are often considered to be patients with emotional and social distress (Wileman et al, 2002). Moreover, professionals often perceive that their relationship with a MUS patient becomes strained when they are unable to provide a physical explanation for the symptoms (Kouyanou et al, 1998; Nettleton, 2006; Wileman et al, 2002); GPs may feel under pressure and powerless in consultations with this group of patients (Harsh et al, 2015; Reid et al, 2001; Wileman et al, 2002).…”
Section: Introduction: Medically Unexplained Symptomsmentioning
confidence: 99%